Assessment of knowledge, awareness and attitudes regarding the re-emerging outbreak of monkeypox among the health professionals in Bangladesh: a web based cross-sectional study - Imran, Faysal Ahmed; Khatun, Mst Eshita; Shahjahan, Md; Chowdhury, ABM Alauddin; Baroi, Liton (International Journal Of Community Medicine And Public Health, 2023)
Background: Before the early 70s, Monkeypox (MPX) was simply recognized as a native disregarded disease in western and central Africa. Moreover, monkeypox is a re-emerging disease that becomes a serious life threatening issue all over the world including non-endemic countries. Regarding the evaluation of research based information about monkeypox in Bangladesh, this study has been conducted to assess the existing knowledge among health professionals. Methods: An online-based cross-sectional study was carried out from 20 June 2022 to 10 August 2022 time period where respondents' knowledge about monkeypox was assessed through using a 21-item scale. The chi-square test was used to make the association between socio-demographic variables and knowledge level. Results: Among 223 respondents, only 53% had good knowledge (mean score >14). Respondents age and sex were significantly correlated with the level of knowledge about monkeypox (p<0.006) and (p<0.02) respectively. Around 72.1% of respondents agreed that the world's populations are able to prevent and control monkeypox worldwide and 65% of respondents believed that media coverage of monkeypox may contribute to global prevention. Moreover, 52.4% respondents had negative attitudes toward monkeypox for becoming a world pandemic. Conclusions: The study finding reveals that knowledge about the monkeypox virus was average and training as well as awareness programs are recommended on monkeypox to promote feather knowledge development among health professionals.